2015
DOI: 10.1111/nyas.12740
|View full text |Cite
|
Sign up to set email alerts
|

Endosymbiont evolution: predictions from theory and surprises from genomes

Abstract: Genome data has created new opportunities to untangle evolutionary processes shaping microbial variation. Among bacteria, long-term mutualists of insects represent the smallest and (typically) most AT-rich genomes. Evolutionary theory provides a context to predict how an endosymbiotic lifestyle may alter fundamental evolutionary processes - mutation, selection, genetic drift, and recombination - and thus contribute to extreme genomic outcomes. These predictions can then be explored by comparing evolutionary ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 144 publications
5
131
0
1
Order By: Relevance
“…A particularly interesting observation regarding replication-related fitness costs is that plasmid DNA is significantly richer in AT than the host chromosome (48,49). This difference is also observed for other "intracellular parasites" such as endosymbionts or phages (48,50). Rocha and Danchin proposed that this bias might reflect the higher energy cost of G and C and the lower availability of these nucleotides in the host cell compared with A and T/U (48).…”
Section: Plasmid Replicationmentioning
confidence: 95%
“…A particularly interesting observation regarding replication-related fitness costs is that plasmid DNA is significantly richer in AT than the host chromosome (48,49). This difference is also observed for other "intracellular parasites" such as endosymbionts or phages (48,50). Rocha and Danchin proposed that this bias might reflect the higher energy cost of G and C and the lower availability of these nucleotides in the host cell compared with A and T/U (48).…”
Section: Plasmid Replicationmentioning
confidence: 95%
“…While a population bottleneck often leads to an explosion of insertion sequences, phage genes, transposable elements, and other mobile elements, it does not necessarily leave these remnants in the contemporary genomes if it occurred anciently. This is well illustrated in the study of endosymbionts, among which the facultative endosymbionts and young obligate endosymbionts (e.g., insect symbionts Sodalis) are often enriched with these genomic features while many of the ancient obligate endosymbionts (e.g., insect symbiont Buchnera) are devoid of them [59]. Even in the very recent transition to obligate mutualism, there are examples in which the mobile elements are rare [60] (e.g., Serratia symbiotica of the cedar aphid).…”
Section: Considering Evolutionary Time Scalementioning
confidence: 98%
“…Although other explanations could be possible (e.g., selection for amino acids with low nitrogen content [67] even if they are physicochemically dissimilar), these results argue for considering drift as an explanation for the ancient evolutionary origin of streamlined genomes in marine bacteria. A recent review, while focusing mainly on endosymbiont evolution, considered alternative evolutionary mechanisms underlying the evolution of free-living marine bacterioplankton, and concluded that a potentially significant role for drift cannot be precluded [59].…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, the genome of Thelohanellus kitauei demonstrates streamlining and loss of genes associated with metabolism [4] but remains eightfold larger, begging the question of why gene loss and compaction is so variable between myxosporeans that both occur as intercellular plasmodia within fish tissues. Possible answers include genome reduction due to genetic drift in isolated populations with small effective population size (for example possible bottlenecking of K. iwatai in the Red Sea), shifts in mutation rate, correlations with cell size or metabolic activity, and reductions in number and activity of transposable elements or in intergenic spacers and introns [5,6].…”
Section: Main Textmentioning
confidence: 99%